Virtual Machines - Craig, Iain D. (Springer London : Imprint: Springer, 2006)
Virtual Machines offers a unique insight into the building of virtual machines for sequential, object-oriented and parallel languages, and uses comparisons of different VMs to provide actual, practical examples on how to build VMs. State transitions are used as a formal technique for the specification of virtual machines throughout and - in addition - transitions and state transitions relating to the general operation are included for specification of the virtual machine for the event-based system. Two virtual machines are defined using a simple sequential language, which is then generalised to include object and parallelism. Other themes explored include the implementation of VMs and proposals for future work. Appendices contain high-level specifications of two compilers: one for the simple language that serves as the basic example throughout the book, the other for the event-based language specified in Chapter 6. This book is an essential reference tool for academic and industrial researchers as well as postgraduates in this area.